A composite thermal insulation plate for a battery pack and a method of manufacturing the same, the battery pack
Patent Information
- Application Number
- CN202611007345.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]然而,这些隔热板存在着诸多问题,包括厚度超标:主流 7 层复合方案厚度通常≥ 2.36mm,难以满足 1.5mm 以下的极致减薄需求;掉粉与封装依赖:传统纳米板易掉粉,必须赖 PI 膜、PET 膜或真空封装,这不仅增加了厚度,且封装膜在高温下易熔毁、产烟;界面失效:多层材料主要通过阻燃胶粘接,在高温和振动工况下极易脱层;遮炎能力弱:现有方案对热失控产生的高压喷射火焰(Jet Flame)冲刷抵御能力不足
[0024]本申请通过材料组分的非均匀空间分布,将具备高消光能力的碳化硅(SiC)定向富集于极薄的迎火层,在入射端构建起一道高效红外屏蔽障。这种设计成功实现了辐射拦截与固相传热阻断的“空间解耦”,既在热源侧尽可能拦截了红外辐射,又避免了高导热SiC 在核心隔热层形成“固体热桥”,从而在 1.5mm 极致厚度下优化了系统的热阻性能。这种解耦设计使厚度低至1.5mm的隔热板的综合隔热性能显著优于相同碳化硅总含量的均匀混合方案。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, and more particularly to a composite heat insulation plate for a battery pack and a method for preparing the same, which is a battery pack. Background Technology
[0002] With the increasing pursuit of energy density in new energy vehicles, the space for battery packs is being compressed, requiring insulation materials to achieve extreme thinning (≤1.5mm) while possessing extremely high fire resistance and heat insulation performance. Current mainstream solutions in the industry include 7-layer composite structures (foam + adhesive + PI film + nano-board, etc.) represented by Deyimeng, and mica sandwich structures represented by Aochuangtexin. In addition, flexible sewn nano-felt and calcium silicate composite boards are also available on the market.
[0003] However, these insulation panels have many problems, including excessive thickness: the mainstream 7-layer composite solution is usually ≥ 2.36mm thick, which is difficult to meet the extreme thinning requirements of less than 1.5mm; powder shedding and encapsulation dependence: traditional nanoplates are prone to powder shedding and must rely on PI film, PET film or vacuum encapsulation, which not only increases the thickness, but also makes the encapsulation film prone to melting and smoke generation at high temperatures; interface failure: multi-layer materials are mainly bonded by flame-retardant adhesives, which are prone to delamination under high temperature and vibration conditions; weak heat shielding ability: existing solutions are not strong enough to resist the impact of high-pressure jet flames generated by thermal runaway.
[0004] Therefore, there is a need for an improved heat insulation plate for battery packs and its preparation method. Summary of the Invention
[0005] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.
[0006] In one aspect, this application provides a composite heat insulation board for a battery pack, the composite heat insulation board comprising a first heat-facing layer, a second heat-facing layer, and a heat insulation layer located between the two heat-facing layers; wherein the percentage of silicon carbide in the first heat-facing layer to the total mass of the first heat-facing layer is A, the percentage of silicon carbide in the second heat-facing layer to the total mass of the second heat-facing layer is B, the percentage of silicon carbide in the heat insulation layer to the total mass of the heat insulation layer is C, A>10C and B>10C, C is a rational number greater than or equal to 0, and A and B are the same or different.
[0007] In one exemplary embodiment, 20% ≤ A ≤ 40%.
[0008] In one exemplary embodiment, 20% ≤ B ≤ 40%.
[0009] In one exemplary embodiment, 0% ≤ C ≤ 2%.
[0010] In an exemplary embodiment, the first heat-receiving layer and the second heat-receiving layer, by weight, comprise 40-50 parts of silica, 20-40 parts of silicon carbide, 8-15 parts of silicone resin, 2-5 parts of silane coupling agent, and 5-10 parts of a first reinforcing material; the heat-insulating layer comprises 90-99 parts of silica, 1-10 parts of a second reinforcing material, and optionally 0-2 parts of silicon carbide.
[0011] In one exemplary embodiment, the silica is fumed nano-silica or silica aerogel.
[0012] In one exemplary embodiment, the silicone resin is an organosilicon resin or an inorganic silicone resin.
[0013] In one exemplary embodiment, the silicone resin is selected from one or more of methyl silicone resin, phenyl silicone resin, and methylphenyl silicone resin.
[0014] In an exemplary embodiment, the silane coupling agent is selected from one or more of KH-570, hexamethyldisilazane, KH-550 (γ-aminopropyltriethoxysilane), KH-560 (γ-(2,3-epoxypropoxy)propyltrimethoxysilane), and KH-792.
[0015] In one exemplary embodiment, the first reinforcing material is selected from one or more of high-silica fibers, ceramic fibers, or polyimide fibers with a length of 3-5 mm.
[0016] In one exemplary embodiment, the second reinforcing material is selected from one or more of chopped ceramic fibers, glass fibers, and alumina fibers.
[0017] In an exemplary embodiment, the thickness of the first heat-receiving layer and the second heat-receiving layer is 0.1-1.0 mm, the thickness of the heat insulation layer is 0.5-2.0 mm, and the total thickness of the composite heat insulation board is 0.7-4.0 mm.
[0018] In an exemplary embodiment, the thickness of the first heat-receiving layer and the second heat-receiving layer is 0.25-0.35 mm, the thickness of the heat insulation layer is 0.8-1.0 mm, and the total thickness of the composite heat insulation board is 1.0-1.5 mm.
[0019] On the other hand, this application provides a method for preparing the above-mentioned composite heat insulation board, the method comprising the following steps: 1) Mix silicon dioxide, silicon carbide, silicone resin, silane coupling agent and the first reinforcing material, and add water to prepare a wet material for the heat-facing layer; 2) Mix silica with the second reinforcing material to form a dry insulation layer; 3) Apply 0.12-0.18 kg / m² to the release liner. 2 The amount of wet material applied to the first heat-facing layer; 4) Apply 0.24-0.30 kg / m² of wet material to the first heat-facing layer. 2 The amount of dry material used to coat the insulation layer; 5) Apply 0.12-0.18 kg / m² to the dry material of the insulation layer. 2 Apply the wet material to the second heat-facing layer; 6) Integrated hot pressing is performed at 120℃-150℃ and 4-6 MPa pressure; and 7) Perform gradient sintering and curing.
[0020] In an exemplary embodiment, in step 6), the integrated hot pressing includes pressing three layers at a temperature of 120-150°C and a pressure of 4-6 MPa.
[0021] In one exemplary embodiment, the release substrate can be a release film, release steel strip, or other easily peelable substrate.
[0022] In an exemplary embodiment, in step 7), the gradient sintering curing includes: Within a temperature range of 120℃-150℃, the heating rate is 2-5℃ / min, and the holding time is 30-60min; Within a temperature range of 140℃-450℃, the heating rate is 5-10℃ / min, and the holding time is 30-60min. Within a temperature range of 400℃-550℃, the heating rate is 5-10℃ / min, and the holding time is 60-120min.
[0023] On the other hand, this application provides a battery pack including a plurality of battery cells separated by the above-described composite heat insulation plate or a composite heat insulation plate prepared by the above method.
[0024] This application utilizes a non-uniform spatial distribution of material components to directionally enrich silicon carbide (SiC) with high extinction capabilities in an extremely thin fire-facing layer, constructing a highly efficient infrared shield at the incident end. This design successfully achieves "spatial decoupling" between radiation interception and solid-phase heat transfer blocking, intercepting infrared radiation as much as possible on the heat source side while avoiding the formation of a "solid thermal bridge" by the high thermal conductivity SiC in the core insulation layer, thereby optimizing the system's thermal resistance performance with an extreme thickness of 1.5 mm. This decoupling design makes the overall thermal insulation performance of the insulation board with a thickness as low as 1.5 mm significantly better than that of a uniformly mixed scheme with the same total silicon carbide content.
[0025] The heat insulation plate prepared in this application significantly improves the mechanical strength in its ultra-thin state, solving the problem of the "fragility" of nanoplates. This application forms a "three-dimensional skeleton-reinforced skin" by incorporating two heat-facing layers and one heat-insulating layer in an ultra-thin structure that can be as thin as 1.5 mm. Compared to traditional homogeneous single-layer nanoplates, this gradient reinforcement structure, while ensuring the core layer's ultimate heat insulation, increases the flexural strength of the 1.5 mm composite plate to 0.5-0.7 MPa (2-3 times higher than traditional dry processes). This effectively solves the problem of breakage of ultra-thin materials during battery packaging and assembly, significantly improving engineering processing performance and yield.
[0026] This application eliminates the risk of delamination under high-temperature conditions by constructing interlayer interface chemical bonds: Addressing the issue of interfacial failure in multilayer composite materials under 1000℃ impact, this application introduces a silane coupling agent into the heat-facing layer, which forms covalent bonds in situ with the fumed silica in the insulation layer during hot pressing. This molecular-level chemical bonding enables the sandwich structure to achieve a "disappearing interface" integrated effect, fundamentally solving the problem of thermal expansion modulus mismatch caused by interlayer composition differences in 1.5mm-sized sheets, ensuring structural integrity under extreme thermal shock.
[0027] This application achieves a film-free self-skinning structure, reducing system thickness and smoke generation risk. By introducing a specific resin into the outer layer and utilizing its in-situ ceramization at high temperatures to form a "film-free" self-skinning structure, this application completely eliminates the need for the polyimide (PI) or other plastic films and adhesive layers that traditional heat insulation pads must cover to prevent powder shedding. This integrated design not only successfully reduces the total thickness of the heat insulation sheet by 20%-30%, freeing up valuable space in the battery pack, but also fundamentally eliminates the secondary disaster risks of traditional organic encapsulation films melting, fueling combustion, and generating large amounts of dense smoke during the initial stages of thermal runaway, significantly improving the overall safety and environmental friendliness of the power battery system.
[0028] The composite insulation board provided in this application has an increased flexural strength of 0.5-0.7 MPa, which solves the problem of the fragility of the 1.5mm ultra-thin board.
[0029] The composite insulation panel provided in this application adopts a film-free design, replacing the PI encapsulation film with a "self-skinning" layer formed by in-situ ceramicization, which reduces the system thickness by 20%-30% and eliminates the risk of smoke generation.
[0030] Other features and advantages of this application will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the application. Other advantages of this application may be realized and obtained by means of the methods described in the description. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application are described in detail below. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be arbitrarily combined with each other.
[0032] Unless otherwise specified, all materials used in the following examples and comparative examples are commercially available.
[0033] Example 1 First heat-receiving layer A wet material ratio: By mass, 45 parts of fumed nano silica, 30 parts of silicon carbide (SiC), 12 parts of methyl silicone resin, 3 parts of silane coupling agent (KH-550) and 10 parts of the first reinforcing material (3mm chopped ceramic fiber) are mixed and water is added to prepare the heat-receiving layer wet material.
[0034] The wet material ratio for the second heat-receiving layer A is as follows: by weight, 45 parts of fumed nano silica, 30 parts of silicon carbide (SiC), 12 parts of methyl silicone resin, 3 parts of silane coupling agent (KH-550) and 10 parts of the first reinforcing material (3mm chopped ceramic fiber) are mixed and water is added to prepare the wet material for the heat-receiving layer.
[0035] Dry material ratio for insulation layer B: Mix 95 parts of fumed nano silica with 5 parts of the second reinforcing material (chopped ceramic fiber) to form the dry material for the insulation layer.
[0036] Fabric processing: Apply 0.15 kg / m² of fabric to the release film (or release steel strip). 2 Apply wet coating material to the heat-facing layer at a rate of 0.27 kg / m². 2 Apply the dry insulation material in an amount equal to 0.15 kg / m². 2 A large amount of wet material is applied to the heat-facing layer to construct an ABA symmetrical structure.
[0037] Pressing at 120℃ and 4 MPa causes elastic deformation between layers and induces interfacial condensation reaction.
[0038] Gradient sintering and curing are performed, including: Stage 1: Solvent removal stage, used to remove solvent and water; Start heating from 120℃ at a rate of 3℃ / min, and hold at 140℃ for 45 minutes. Phase 2: Degradation phase, used to degrade the resin side chains and form preliminary chemical bonds; Start heating from 140℃ at a rate of 7℃ / min, and hold at 400℃ for 60min. Stage 3: Ceramization stage, used to lock covalent bonds and form a skin; Start heating from 400℃ at a rate of 7℃ / min, and hold at 550℃ for 90 minutes.
[0039] After sintering and curing, the release film detaches, forming a composite heat insulation board with a total thickness of 1.5 mm, consisting of a first heat-facing layer of 0.3 mm thickness, a heat insulation layer of 0.9 mm thickness, and a second heat-facing layer of 0.3 mm thickness.
[0040] Example 2 First / Second Heat-Inducing Layer A Wet Material Ratio: Mix 35 parts of fumed nano silica, 40 parts of silicon carbide, 15 parts of phenyl silicone resin, 5 parts of silane coupling agent (KH-560) and 5 parts of 3mm polyimide (PI) fiber.
[0041] Insulation layer B dry material ratio: Mix 92 parts of fumed nano silica with 8 parts of alumina fiber.
[0042] Process conditions: Pressed at 150℃ and 6 MPa.
[0043] Gradient sintering and curing are performed, including: Stage 1: Solvent removal stage, used to remove solvent and water; Start heating from 120℃ at a rate of 5℃ / min, and hold at 150℃ for 60min. Phase 2: Degradation phase, used to degrade the resin side chains and form preliminary chemical bonds; Start heating from 150℃ at a rate of 10℃ / min, and hold at 450℃ for 60 minutes. Stage 3: Ceramization stage, used to lock covalent bonds and form a skin; Start heating from 450℃ at a rate of 7℃ / min, and hold at 550℃ for 120 minutes.
[0044] After sintering and curing, the release film detaches, forming a composite heat insulation board with a total thickness of 1.5 mm, consisting of a first heat-facing layer of 0.3 mm thickness, a heat insulation layer of 0.9 mm thickness, and a second heat-facing layer of 0.3 mm thickness.
[0045] Example 3 First / Second Heat-Inducing Layer A Wet Material Ratio: Mix 55 parts of fumed nano silica, 20 parts of silicon carbide, 10 parts of methyl phenyl silicone resin, 2 parts of KH-550 and 13 parts of high-silica fiber.
[0046] Insulation layer B dry material ratio: Mix 98 parts of fumed nano silica with 2 parts of ceramic fiber.
[0047] Process conditions: Pressed at 120℃ and 4 MPa.
[0048] Gradient sintering and curing are performed, including: Stage 1: Solvent removal stage, used to remove solvent and water; Start heating from 120℃ at a rate of 2℃ / min, and hold at 140℃ for 30 minutes. Phase 2: Degradation phase, used to degrade the resin side chains and form preliminary chemical bonds; Start heating from 140℃ at a rate of 10℃ / min, and hold at 400℃ for 60min. Stage 3: Ceramization stage, used to lock covalent bonds and form a skin; Start heating from 400℃ at a rate of 7℃ / min, and hold at 550℃ for 120 minutes.
[0049] After sintering and curing, the release film detaches, forming a composite heat insulation board with a total thickness of 1.5 mm, consisting of a first heat-facing layer of 0.3 mm thickness, a heat insulation layer of 0.9 mm thickness, and a second heat-facing layer of 0.3 mm thickness.
[0050] Example 4 First / Second Heat-Resistant Layer A Wet Material Ratio: By mass, mix 45 parts of fumed nano silica, 30 parts of silicon carbide, 12 parts of methyl silicone resin, 3 parts of silane coupling agent (KH-550) and 10 parts of the first reinforcing material (3mm chopped ceramic fiber), and add water to prepare the heat-resistant layer wet material.
[0051] Dry material ratio for insulation layer B: Mix 93 parts of fumed nano silica, 5 parts of the second reinforcing material (chopped ceramic fiber) and 2 parts of silicon carbide to form the dry material for the insulation layer.
[0052] Process conditions: Pressed at 140℃ and 5 MPa, and then subjected to gradient sintering and curing in three stages according to Example 1 (maximum temperature 550℃).
[0053] After sintering and curing, the release film detaches, forming a composite heat insulation board with a total thickness of 1.5 mm, consisting of a first heat-facing layer of 0.3 mm thickness, a heat insulation layer of 0.9 mm thickness, and a second heat-facing layer of 0.3 mm thickness.
[0054] Comparative Example 1 This comparative example does not include the intermediate heat insulation layer. Instead, it is prepared by uniformly mixing the components of the heat-facing layer in Example 1 and using the same hot pressing and gradient heat treatment process as in Example 1, ultimately forming a composite heat insulation board with a total thickness of 1.5 mm and silicon carbide uniformly distributed in an amount of 15 wt%.
[0055] Comparative Example 2 This comparative example only has one 0.3mm heat-facing layer and one 1.2mm heat-insulating layer. It is prepared using the same hot-pressing and gradient heat treatment process as Example 1.
[0056] Comparative Example 3 The formulation of this comparative example is the same as that of Example 1, but the silane coupling agent has been removed from the heat-facing layer (no coupling agent chemical bonding). Except for the removal of the silane coupling agent from the heat-facing layer, the other components and heat treatment processes are the same as those in Example 1.
[0057] Performance testing The composite insulation panels prepared in the examples and comparative examples were subjected to the following tests: Flexural strength test: The test was conducted using the three-point bending method, in accordance with GB / T 3003-2017. Temperature rise test of cold surface after 10 minutes of 1000℃ flame: Using a butane flame torch, the flame temperature was set to 1000±50℃, and the nozzle was 50mm away from the heated surface of the sample. The temperature rise curve of the center of the cold surface was tested within 10 minutes.
[0058] Interface bonding status: Visually observe the surface powdering and self-skinning.
[0059] The test results are shown in Table 1 below.
[0060] Table 1 As can be seen from the results in Table 1, the ABA symmetric structure with a silicon carbide mass gradient of 30%-0%-30% used in the first embodiment of this application successfully achieved spatial decoupling between infrared radiation interception (A layer) and solid-phase heat transfer blocking (B layer), ensuring structural stability and bidirectional protection capability.
[0061] This application introduces a silane coupling agent into the heat-facing layer, which forms chemical bonds with the nanoparticles of the heat-insulating layer through a condensation reaction during the pressing process, eliminating the physical interface and achieving interfacial covalent bonding (≡Si-O-Si≡), thus solving the problem of delamination of ultrathin structures under extreme thermal shock.
[0062] This application employs a double-sided high-extinction shielding heat-facing layer, achieving efficient interception of infrared radiation above 1000℃ within a thickness of 0.3mm.
[0063] This application achieves in-situ ceramic self-skinning by utilizing the ceramic transformation of the resin in the heat-facing layer at high temperatures to achieve anti-powdering and flame erosion resistance without an encapsulation film.
[0064] The comparison between Example 1 and Comparative Example 3 in this application strongly demonstrates the decisive role of silane coupling agents in forming covalent bonds at the molecular level to enhance the integrated strength of ultra-thin sheet materials.
[0065] As can be seen from Example 2, the highest flexural strength (0.72 MPa) was obtained when the silicon carbide (SiC) content in the heat-facing layer increased to 40 wt%. If the silicon carbide (SiC) content in the heat-facing layer is further increased, the "solid thermal bridge effect" caused by the excessively high concentration of high thermal conductivity SiC particles in the extremely thin skin layer will begin to offset its extinction shielding gain, resulting in excessive temperature rise on the cold side.
[0066] Example 3 shows that when the silicon carbide (SiC) content in the heat-facing layer is as low as 20 wt%, its cold surface temperature rise of 198°C is still significantly better than that of Comparative Example 1 (245°C), which has a similar SiC content but uses a homogeneous distribution. It can still effectively solve the problem of thermal insulation failure of ultrathin nanoplates under extreme thinning conditions.
[0067] Furthermore, in Example 4, 2 wt% silicon carbide was introduced into the insulation layer. Due to the solid thermal bridging effect generated by the opaque agent in the pure nanopores, the cold surface temperature rise after 10 minutes of 1000°C flame firing was slightly increased from 185°C (Example 1), and the flexural strength was improved to 0.67 MPa. This still effectively solved the problem of insulation failure of the ultrathin nanoplate under extreme thinning conditions. If the amount of silicon carbide in the insulation layer is further increased, this will lead to an excessively high cold surface temperature rise after 10 minutes of 1000°C flame firing, and the insulation failure problem cannot be effectively solved.
[0068] In contrast, Comparative Example 1, due to its homogeneous mixed structure, has SiC uniformly distributed throughout its thickness, resulting in a significant "solid thermal bridge effect" in the core region. At the same time, because its surface SiC concentration is low (only 15wt%), it fails to construct an effective infrared shield to intercept infrared radiation as much as possible at the incident end, leading to a significant decrease in thermal resistance performance.
[0069] In Comparative Example 2, thermal runaway could originate from either side of the battery pack. In the asymmetric structure facing the heat source on the back, the lack of a "ceramicated self-skin" protection from the insulation layer means the insulation layer is directly exposed to the flame and will rapidly pulverize, collapse, and be blown away by the jet stream.
[0070] In Comparative Example 3, since the interlayer bonding relies solely on the physical stacking of particles, the interfacial bonding force is weak (only about 30% of that in Example 1). Under the pressure scouring of the 1000°C flame test, significant interlayer peeling and failure occurred.
[0071] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A composite heat insulation board for a battery pack, characterized in that, The composite heat insulation board includes a first heat-facing layer, a second heat-facing layer, and a heat insulation layer located between the two heat-facing layers; The percentage of silicon carbide in the first heat-receiving layer to the total mass of the first heat-receiving layer is A, the percentage of silicon carbide in the second heat-receiving layer to the total mass of the second heat-receiving layer is B, and the percentage of silicon carbide in the insulation layer to the total mass of the insulation layer is C, where A > 10C and B > 10C, C is a rational number greater than or equal to 0, and A and B are the same or different.
2. The composite heat insulation board according to claim 1, characterized in that, It also includes at least one of the following: 20%≤A≤40%; 20%≤B≤40%; 0%≤C≤2%.
3. The composite heat insulation board according to claim 1 or 2, characterized in that, The first heat-receiving layer and the second heat-receiving layer, by weight, comprise 40-50 parts of silicon dioxide, 20-40 parts of silicon carbide, 8-15 parts of silicone resin, 2-5 parts of silane coupling agent, and 5-10 parts of first reinforcing material; the heat insulation layer comprises 90-99 parts of silicon dioxide, 1-10 parts of second reinforcing material, and optionally 0-2 parts of silicon carbide.
4. The composite heat insulation board according to claim 1 or 2, characterized in that, The silica is fumed nano-silica or silica aerogel; and / or, The silicone resin is an organic silicone resin or an inorganic silicone resin; and / or, The silane coupling agent is selected from one or more of KH-570, hexamethyldisilazane, KH-550, KH-560, and KH-792; and / or, The first reinforcing material is selected from one or more of high-silica fibers, ceramic fibers, or polyimide fibers with a length of 3-5 mm; and / or, The second reinforcing material is selected from one or more of chopped ceramic fibers, glass fibers, and alumina fibers.
5. The composite heat insulation board according to claim 4, characterized in that, The organosilicon resin is selected from one or more of methyl silicone resin, phenyl silicone resin, and methylphenyl silicone resin.
6. The composite heat insulation board according to claim 1 or 2, characterized in that, The thickness of the first heat-receiving layer and the second heat-receiving layer is 0.1-1.0 mm each, the thickness of the heat insulation layer is 0.5-2.0 mm, and the total thickness of the composite heat insulation board is 0.7-4.0 mm. Optionally, the thickness of the first heat-facing layer and the second heat-facing layer is 0.25-0.35 mm, the thickness of the heat insulation layer is 0.8-1.0 mm, and the total thickness of the composite heat insulation board is 1.0-1.5 mm.
7. A method for preparing a composite heat insulation board according to any one of claims 1-6, characterized in that, The method includes the following steps: 1) Mix silicon dioxide, silicon carbide, silicone resin, silane coupling agent and the first reinforcing material, and add water to prepare a wet material for the heat-facing layer; 2) Mix silica with the second reinforcing material to form a dry insulation layer; 3) Apply 0.12-0.18 kg / m² to the release liner. 2 The amount of wet material applied to the first heat-facing layer; 4) Apply 0.24-0.30 kg / m² of wet material to the first heat-facing layer. 2 The amount of dry material used to coat the insulation layer; 5) Apply 0.12-0.18 kg / m² to the dry material of the insulation layer. 2 Apply the wet material to the second heat-facing layer; 6) Integrated hot pressing is performed at 120℃-150℃ and 4-6 MPa pressure; as well as 7) Perform gradient sintering and curing.
8. The method according to claim 7, characterized in that, In step 6), the integrated hot pressing includes pressing three layers at a temperature of 120-150°C and a pressure of 4-6 MPa.
9. The method according to claim 7, characterized in that, The gradient sintering and solidification includes: Within a temperature range of 120℃-150℃, the heating rate is 2-5℃ / min, and the holding time is 30-60min; Within a temperature range of 140℃-450℃, the heating rate is 5-10℃ / min, and the holding time is 30-60min. Within a temperature range of 400℃-550℃, the heating rate is 5-10℃ / min, and the holding time is 60-120min.
10. A battery pack, characterized in that, It includes a plurality of battery cells separated by a composite insulation panel as described in any one of claims 1-6 or a composite insulation panel prepared by the method described in any one of claims 7-9.